Proceedings of the 24th Australian Computer-Human Interaction Conference 2012
DOI: 10.1145/2414536.2414638
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the usability of grid-bag and constraint-based layouts

Abstract: While the usability of GUI design methods has been studied in general, the usability of layout specification methods is largely unexplored.In this paper we provide an empirical comparison of two popular GUI layout models, grid-bag layout and constraint-based layout. While the grid-bag layout is a powerful layout model, the constraint-based layout is able to generate even more general and flexible layout configurations. We performed a controlled experiment with postgraduate students of Computer Science and Soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…For this comparison we chose the GUI builder in MS Visual Studio 2010 (VS) as a representative for the state of the art, since it was popular at the time of the study. A prior study compared the usability of the gridbag and the constraint-based layout model, finding that the gridbag layout model has advantages in the creation of new layouts [19]. This supports our choice of a gridbag GUI builder such as VS for comparison with ALE when investigating H1.…”
Section: Experiments 1: Comparison With a Gridbag Gui Buildersupporting
confidence: 55%
See 1 more Smart Citation
“…For this comparison we chose the GUI builder in MS Visual Studio 2010 (VS) as a representative for the state of the art, since it was popular at the time of the study. A prior study compared the usability of the gridbag and the constraint-based layout model, finding that the gridbag layout model has advantages in the creation of new layouts [19]. This supports our choice of a gridbag GUI builder such as VS for comparison with ALE when investigating H1.…”
Section: Experiments 1: Comparison With a Gridbag Gui Buildersupporting
confidence: 55%
“…A previous usability comparison between constraint-based and grid-based layout models [19] used printed screenshots and sketching. This comparison found that the constraint-based layout model is a competitive alternative to the grid-bag layout model and performs better for editing existing layouts.…”
Section: Related Workmentioning
confidence: 99%
“…A benefit of constraint solving is that a layout can be defined by means of simple constraints. On the other hand, specifying a layout fully using just constraints quickly becomes complex [61]. To our knowledge, no constraints-based method has been proposed that ensures proper packing of elements and takes care of objectives like alignment, rectangularity, and grouping.…”
Section: Grid Generation By Constraint Solvingmentioning
confidence: 99%
“…Constraintbased layouts, such as Auto Layout 4 , are often used to make a layout resizable [8,[36][37][38]. Hottelier et al [39] proposed a technique which allows designers to generalize and specialize constraint-based layout specifications using direct manipulation.…”
Section: Related Workmentioning
confidence: 99%